2006
DOI: 10.1080/00365590600621261
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hypercalcic and/or hyperoxalic diet on calcium oxalate renal stone formation in rats

Abstract: Increased dietary calcium intake can prevent calcium oxalate stone formation only when the diet is oxalate-rich.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Restriction of dietary calcium intake proved less effective than salt and protein restriction in preventing kidney stone recurrence [62]. However, the effect of dietary calcium on stone-forming propensity also depends on the oxalate content of the diet (i.e., the calcium/oxalate balance) and on the timing of calcium consumption [99,[119][120][121]. In fact, stone formers have a higher fractional intestinal calcium absorption than subjects not suffering from nephrolithiasis, and foods with high calcium content should be consumed during balanced meals to protect against the risk of hypercalciuria [122][123][124].…”
Section: Calcium Intake and Microbiotamentioning
confidence: 99%
“…Restriction of dietary calcium intake proved less effective than salt and protein restriction in preventing kidney stone recurrence [62]. However, the effect of dietary calcium on stone-forming propensity also depends on the oxalate content of the diet (i.e., the calcium/oxalate balance) and on the timing of calcium consumption [99,[119][120][121]. In fact, stone formers have a higher fractional intestinal calcium absorption than subjects not suffering from nephrolithiasis, and foods with high calcium content should be consumed during balanced meals to protect against the risk of hypercalciuria [122][123][124].…”
Section: Calcium Intake and Microbiotamentioning
confidence: 99%
“…Experiments in rats have suggested that increased dietary calcium intake can prevent calcium oxalate stone formation only when the diet is oxalate rich. 7 Of late, our group has noticed an increase in the prevalence of nephrolithiasis in our patients who have undergone RYGBP, with the calculi predominantly calcium oxalate. Considering the relative dearth of literature discussing the association between enteric hyperoxaluria= nephrolithiasis and Roux en Y procedures, we determined that sharing our observations and experience in the form of a case study was both a necessary contribution to the literature and an important means of understanding and raising awareness of the increased risks of these conditions.…”
Section: Introductionmentioning
confidence: 96%